The impact of acute stress on athletes’ perceptions of fairness in decision-making and its neural mechanisms - Ji, Jiayuan; Wang, Huiling; Wang, Shiyu; Ye, Yutong; Zhang, Yitong; Li, Lin (Frontiers in Human Neuroscience, 2025)
BackgroundAcute stress may disrupt decision - making by affecting cognitive and emotional processing. The behavioral and neural mechanisms of this in athletes are unclear. This study explored how acute stress impacts athletes’ unfairness - related decision - making and its neural basis.MethodsForty participants (20 university athletes and 20 non-athletes) were randomly assigned to a stress group or a control group. Using functional near-infrared spectroscopy (fNIRS), the study monitored the prefrontal cortex (PFC) and temporoparietal junction (TPJ) blood oxygenation during an ultimatum game task after inducing acute stress via the Maastricht Acute Stress Test (MAST).ResultsAthletes under stress were more accepting of relatively unfair decisions than non-athletes. This was linked to lower activation in the frontal-eye areas (CH15), supramarginal gyrus (CH38), and somatosensory association cortex (CH67), and higher activation in the primary motor cortex (CH64) in athletes. The increase in acceptance efficiency correlated significantly with the reduced CH38 activation (r = −0.425) and increased CH64 activation (r = 0.499).ConclusionLong-term exercise training may promote athletes’ tendency to accept relatively unfair decisions under acute stress by modulating activation levels in the supramarginal gyrus and primary motor cortex, demonstrating stronger adaptive behavior. These findings offer insights for developing stress management and neuromodulation training programs for athletes.